Tutela de evidência sancionatória sob a perspectiva do juiz - Kiefer, Kelly (2018)
It studies, from the point of view of the magistrate, the applicability of art. 311, I of CPC / 15, which deals with the grant of protection of evidence in the hypothesis of abuse of the right of defense or manifest protelatory purpose of the defendant. The objective is to identify the obstacles to the application of the norm and, based on a bibliographical and jurisprudential research, propose suitable measures to guarantee the effectiveness of the norm, presupposing a publicist conception of the process in which ethical elements emerge based on objetive good faith principle and procedural loyalty. It develops the subject from the historical analysis of the protection of evidence up to the present day and makes an approach to the treatment conferred on the institute in both the ordering, the doctrine and the patriotic courts to find the reasons why the norm has little applicability. It then correlates the issue with the abuse of procedural law and the judge’s powers. It concludes by the need to give greater attention to the behavior of the procedural participantes in order to prevent and inhibit abusive conduct, possibly granting immediately the good of life to the injured part, as long as it presents the probability of the alleged right.